Estudo sobre suicídio e tentativa de suicídio entre adolescentes em Campo Grande/MS - Silva, Ady Faria da (2022)
Exposure to violence in its different presentations and the search for identity increase vulnerability in adolescence and compromise the health and development of this population. In this case, the present study has as its theme suicide and attempted suicide among adolescents in Campo Grande/MS. Considering that it is essential to understand the dynamics of this phenomenon, to support coping strategies and considering risk factors, the objective was to analyze and describe suicide and attempted suicide among adolescents in Campo Grande/MS. For this, a retrospective, cross-sectional ecological study was carried out with secondary data. Data released by DATASUS from 2015 to 2019 on attempted suicide show a growth of 40.1%, while suicide rates exceeded 30%. The prevalence of suicides in relation to attempts shows a decreasing trend from 2017 onwards. Suicide attempts showed an increase and suicides remained stable over the same period. Regarding the filling out of the forms by health professionals, there is confusion in the type of information to be entered, as there is repeated information from specific fields. The poor completion of these forms does not make it clear the cause that leads the adolescent to commit such an act or whether this adolescent undergoes psychological counseling or not. Also, in cases of recurrence of a suicide attempt, which measures were adopted. In this context, the SINAN form used to fill in other types of violence has a gap in terms of filling in the suicide attempt. Thus, it can be observed that the results found can contribute to the generation of actions and intersectoral assistance policies, aiming to reduce risk factors for the disease.